PEMBELAJARAN TRANSFORMATIF MELALUI MODALITY EMBODIED PADA PEMERLU ATENSI SOSIAL DALAM PROGRAM VOKASIONAL BATIK CIPRAT - Mutiara Velisa Mutiara; Ari Putra; Nia Ulfasari (Comm-Edu (Community Education Journal), 2026)
This study investigates transformative learning among Persons in Need of Social Attention (PAS) with significant cognitive and psychosocial limitations through participation in the Batik Ciprat vocational program at Sentra Dharma Guna, Bengkulu. While Mezirow’s transformative learning theory emphasizes critical reflection as the basis of personal transformation, this research examines how transformation may occur when learners have limited capacity for abstract reasoning. A qualitative case study design was employed over a two-month period using participatory observation, in-depth interviews with instructors and PAS participants, and analysis of batik products. The findings reveal a meaningful shift in participants’ self-perception from viewing themselves as incapable to recognizing themselves as productive creators. This transformation emerged through five interconnected processes: repeated hands-on engagement in producing marketable batik, the accumulation of successful learning experiences, continuous cognitive reframing by instructors and caregivers, social affirmation through recognition from the surrounding community, and the incorporation of a new identity into everyday practices. The study extends transformative learning theory by demonstrating that personal transformation can develop through embodied, emotional, and relational experiences rather than relying solely on abstract critical reflection. These findings underscore the importance of accessible learning environments, sustained emotional support, and positive social recognition in facilitating transformative learning for marginalized individuals with cognitive limitations.